Nutritional Content of Green Algae Caulerpa racemosa and Brown Algae Sargassum polycystum at Ranowangko II Beach, Kombi District, Minahasa Regency - Rorong, Joana Hope; Rampengan, Mercy Maggy Franky; Roring, Verawati Ida Yani; Ogi, Nova Laurin Isye Mourein (RUMPHIUS, 2024)
Ranowangko II beach is famous for its beautiful beaches and is a natural habitat for macroalgae, including Caulerpa racemosa and Sargassum polycystum. Despite its great potential and abundance, information about the nutritional content of both types of algae, especially in the Ranowangko II beach area, is still limited. This study aimed to determine the nutritional content (water content, ash content, protein, lipid, crude fiber, carbohydrate) of green algae Caulerpa racemosa and brown algae Sargassum polycystum in Ranowangko II beach. The type of research used is descriptive quantitative to determine the proximate nutrient content of two types of algae tested by proximate analysis in the laboratory. Based on the study results, there were variations in the nutritional content of the two types of algae tested. Green algae Caulerpa racemosa has a moisture content of 71.29%, ash content of 6.90%, protein of 2.78%, fat of 1.34%, crude fiber of 3.53%, and carbohydrates of 17.69%. Brown algae Sargassum polycystum has a water content of 83.23%, ash content of 1.82%, protein of 9.93%, fat of 1.72%, crude fiber of 11.18%, and carbohydrates of 3.30%. The conclusion obtained after conducting this research is that Caulerpa racemosa (green algae) and Sargassum polycystum (brown algae) have different nutritional content.